Environmental Occurrence, Toxicity and Mitigation Strategies of Micro-Plastics in the Aquatic Ecosystem - Jacob, U. S; Isangedighi, I. A.; O. A, Akangbe; U. E , Jonah, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
The presence and occurrence of micro-plastics in aquatic ecosystems significantly impact the structure, organism functions, and aesthetic values of the ecosystem. An extensive search of databases such as PubMed, Scopus, Web of Science, Science Direct, Google Scholar, and African Journals Online was conducted to gather relevant research reports on microplastics. Microplastics are typically classified into primary and secondary microplastics originating from microbeads used in cosmetics, the ship-breaking industry, fertilizers, and indiscriminate waste disposal. Plastic pollution in aquatic ecosystems poses a serious threat to aquatic organisms through entanglement, ingestion, and exposure to toxic plastic additives. Plastic additives can lead to oxidative stress, gastrointestinal obstruction, translocation, and trophic transfer. Bisphenol-A and phthalates, critical components of plastic, have serious endocrine-disrupting effects on organisms. Mitigation strategies to reduce plastic and microplastic pollution require interventions from governments at all levels to establish effective waste management programs, policies, and regulations. Designing eco-friendly and biodegradable plastic products is crucial for effective plastic waste management. Furthermore, remediating contaminated environments using eco-friendly methods is essential to address microplastic pollution in the aquatic ecosystem without imposing severe ecological risks. microplastics